Cerebrospinal fluid and optic nerve sheath compartment syndrome: A common pathophysiological mechanism in five different cases?. (11th November 2019) - Hao, Jie; Pircher, Achmed; Miller, Neil R.; Hsieh, Jiemei; Remonda, Luca; Killer, Hanspeter E.
Abstract: Importance: Optic nerve (ON) dysfunction is a common feature of different diseases. The pathophysiology is not yet fully understood. Background: This study describes five patients with ON sheath (ONS) compartment syndrome (ONSCS) and contributes to the hypothesis that impaired cerebrospinal fluid (CSF) flow can play a role in the development of ON dysfunction. Design: Retrospective case series. Participants: Five patients with ONSCS were included in the study. Methods: Elaboration of medical histories and clinical and diagnostic findings over a long time period was carried out by analysing medical records and by a detailed medical consultation. Main Outcome Measures: The main outcome measures include clinical history; visual acuity; field, intraocular and CSF pressures; and contrast‐loaded computed tomographic (CT) cisternography. Results: Compartmentation of the ONS demonstrated by contrast‐loaded CT cisternography was the consistent finding in all five patients who demonstrated findings of ON dysfunction. The aetiologies varied and included meningitis, papilloedema, sphenoid wing meningioma, disc herniation and normal‐tension glaucoma. Conclusion and Relevance: Compartmentation of the ONS with consecutively impaired CSF dynamics within the ON subarachnoid space can lead to ON dysfunction. Different aetiologies can cause the development of ONSCS.